2020
DOI: 10.2147/jpr.s255250
|View full text |Cite
|
Sign up to set email alerts
|

<p>Role of Dopaminergic Receptors Within the Ventral Tegmental Area in Antinociception Induced by Chemical Stimulation of the Lateral Hypothalamus in an Animal Model of Orofacial Pain</p>

Abstract: Introduction:The ventral tegmental area (VTA), as one of the classical components of the brain reward circuitry, shares large neural networks with the pain processing system. We previously showed the role of VTA dopamine receptors in modulation of lateral hypothalamus (LH)-induced antinociception in acute pain conditions. However, considering the fact that the neural systems involved in the mediation of tonic pain are not the same as those that mediate phasic pain. In the present study, we aimed to examine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…The present study results demonstrated that blockade of dopamine receptors within the DG region could completely block the antinociceptive responses induced by chemical stimulation of LH following formalin injection into the orofacial region. In this regard, the previous study revealed that the dopaminergic receptors located in the VTA contributes in antinociception induced by chemical stimulation of LH during orofacial pain in rats (Matini et al, 2020). In addition, the role of dopaminergic receptors in the NAc in antinociceptive response-induced by chemical stimulation of LH has been demonstrated in formalin-induced orofacial pain (Shafiei et al, 2018).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The present study results demonstrated that blockade of dopamine receptors within the DG region could completely block the antinociceptive responses induced by chemical stimulation of LH following formalin injection into the orofacial region. In this regard, the previous study revealed that the dopaminergic receptors located in the VTA contributes in antinociception induced by chemical stimulation of LH during orofacial pain in rats (Matini et al, 2020). In addition, the role of dopaminergic receptors in the NAc in antinociceptive response-induced by chemical stimulation of LH has been demonstrated in formalin-induced orofacial pain (Shafiei et al, 2018).…”
Section: Discussionmentioning
confidence: 95%
“…Besides, a positron emission tomography (PET) study on patients with burning mouth syndrome showed a decrease in the D1/ D2 ratio and dopamine hypofunction in the nigrostriatal dopaminergic pathway (Hagelberg et al, 2003). It has been shown that dopaminergic receptors within the VTA (Matini et al, 2020) and NAc (Haghparast et al, 2020) modulate the antinociceptive responses induced by chemical stimulation of the LH in an animal model of orofacial pain.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the arousal effect, we found that activating orexin neurons in the lateral hypothalamus can increase the animal’s tolerance to painful stimuli. Many of the orexin projected brain regions are also involved in the pain control, such as BST, central amygdala nucleus, dorsal nucleus raphe, laterodorsal tegmental area, lateral habenula, PAG, parabrachial nucleus, PVT, and VTA, which may underlie the analgesic effects by orexin neurons ( Kooshki et al, 2020 ; Matini et al, 2020 ). Further work is needed to study the involvement of different nuclei in pain control.…”
Section: Discussionmentioning
confidence: 99%
“…LH stimulation could also reduce hyperalgesia through orexin-A neurons in an animal model of neuropathic pain (Wardach et al , 2016). Moreover, the effect of LH stimulation on dopaminergic receptors within the VTA in attenuating orofacial pain has also been demonstrated (Matini et al , 2020). Orexin neurons project from the LH to dopaminergic neurons in the VTA, and VTA dopamine neurons project to the nucleus accumbens (NAc), amygdala, hippocampus, and prefrontal cortex, forming the mesocorticolimbic dopamine system (Korotkova et al , 2003).…”
Section: Introductionmentioning
confidence: 99%